PENGARUH KEMASAN DAN HARGA TERHADAP NIAT BELI KONSUMEN PADA PERUSAHAAN POD CHOCOLATE - Asmara Putra, Komang Elmar Datraja; Rastini, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Purchase intention can be formed because of the influence of some factores, namely expected income, expected price, and expected product's benefits. Attractive packaging is one of the ways that is used by the enterpreneurs to catch consumer's purchase intention. price also take control to affect consumer's purchase intention. This research has purpose to explain the influence of the packaging and product's price toward purchase intention in POD Chocolate. The design of this research was using quantitave method, in the form of associative. This research was done in Denpasar City. Sample deciding method that was used is purposive sampling technique with 90 respondents from Denpasar City's resident that have not bought the product of POD Chocolate. The technique of analysing data that was used is multiple linear regression. The findings showed that (1) packaging had positive significant influence towards purchase intention, (2) price had positive significant influence towards purchase intention.These findings are expected to be able to support POD Chocolate or other chocolate company to maintain the consumers and improve potential consumers by knowing the causes of consumers purchase intention